David Atlee Phillips papers - Phillips, David Atlee
Correspondence, memoranda, manuscripts and typescripts of books and articles, speech, reports, research material, court documents, biographical notes, and other papers pertaining primarily to Phillips's career in the U.S. Central Intelligence Agency dealing chiefly with Latin American affairs. Subjects include Phillips's captivity and escape from a Nazi prisoner-of-war camp; charges of Phillips's involvement in the assassinations of President John F. Kennedy and Orlando Letelier; and William Niehous's kidnapping and captivity by Venezuelan radicals. Correspondents include Joseph C. Goulden.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Library of Congress Serial and Government Publications Division.
Newspaper publisher, intelligence officer, and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Goulden, Joseph C. -- Correspondence; Kennedy, John F. -- 1917-1963 -- Assassination; Letelier, Orlando -- Assassination; Niehous, William Frank, -- 1931-2013.; United States. -- Central Intelligence Agency; Kidnapping -- Venezuela; Terrorism -- Venezuela; World War, 1939-1945 -- Prisoners and prisons, German; Latin America -- Foreign relations -- United States; United States -- Foreign relations -- Latin America; Authors; Intelligence officers; Publishers